2014
DOI: 10.1002/stvr.1527
|View full text |Cite
|
Sign up to set email alerts
|

Automatic test case evolution

Abstract: SUMMARYSoftware systems evolve incrementally both during and after development, and many test cases become obsolete while software evolves. Updating test suites in the context of software evolution is a complex and time consuming activity. This article focuses on the problem of updating test suites automatically, and identifies eight scenarios that allow either to repair test cases or to use test cases to generate new ones, and proposes eight test evolution algorithms that automatically repair and generate tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Fornari, Glenford J. Myers and Mehdi Mirzaaghaei showed that software testing is a creative and critical activity that requires discipline and software engineering expertise. It is an activity where you have to imagine the scenarios capable of causing the software to fail, and to build the simulation environments, but it is wrongly perceived as the tester is usually at the end of the chain, which generally causes the delays [4] [5] [19].…”
Section: Generalities On Software Testingmentioning
confidence: 99%
“…Fornari, Glenford J. Myers and Mehdi Mirzaaghaei showed that software testing is a creative and critical activity that requires discipline and software engineering expertise. It is an activity where you have to imagine the scenarios capable of causing the software to fail, and to build the simulation environments, but it is wrongly perceived as the tester is usually at the end of the chain, which generally causes the delays [4] [5] [19].…”
Section: Generalities On Software Testingmentioning
confidence: 99%